1976
DOI: 10.1139/y76-124
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin contamination as a cause of some apparent renal actions of prolactin

Abstract: The injection or infusion of NIAMDD prolactin (NIH P-S-10) into unanesthetized rats resulted in water and electrolyte retention with a large increase in urine osmolality but no effect on glomerular filtration rate. Since these effects on urine output were also observed in homozygous Brattleboro rats, the antidiuretic activity could not have caused by the release of endogenous antidiuretic hormone. Radioimmunoassay of NIH prolactin showed that it was contaminated with vasopressin (20 ng/mg of prolactin). By com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Vasopressin, an antidiuretic hormone, and oxytocin, important in milk ejection, have been shown to be present in one prolactin preparation (NIH-P-SIO) (Keeler & Wilson, 1976;Bond, Pasley, Koike & Llerena, 1976) and could affect cation flux in mammary tissue. The results show no effects on ion transport due to vasopressin or oxytocin at the concentration reported in NIH-P-S10 prolactin, or at 10-fold higher concentration (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasopressin, an antidiuretic hormone, and oxytocin, important in milk ejection, have been shown to be present in one prolactin preparation (NIH-P-SIO) (Keeler & Wilson, 1976;Bond, Pasley, Koike & Llerena, 1976) and could affect cation flux in mammary tissue. The results show no effects on ion transport due to vasopressin or oxytocin at the concentration reported in NIH-P-S10 prolactin, or at 10-fold higher concentration (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Effect of vasopressin and oxytocin on 86Rb+ uptake and K+ content of mammary slices Vasopressin and oxytocin have been found in some prolactin preparations (NIH-P-S10) (Keeler & Wilson, 1976;Bond, Pasley, Koike & Llerena, 1976). Vasopressin and oxytocin were tested in place of prolactin to see if the observed changes in 86Rb+ uptake or total K+ content could be due to their contamination of the prolactin used.…”
mentioning
confidence: 99%
“…The evidence that injected prolactin does influence water and electrolyte excretion is controversial especially since it has been found that some of the preparations of prolactin are contaminated with vasopressin (Vorherr, Vorherr & Solomon, 1978). Thus Keeler & Wilson (1976) and Carey, Johanson & Seit (1977) found that, when vasopressin-free prolactin was used, there was no evidence for antidiuretic activity and indeed El Karib & Green 1981) have shown that prolonged administration of prolactin injected s.c. can increase glomerular filtration rate. However, Kaufman, Mackay & Scott (1981) found that, although urine output was greater in rats bearing ectopic pituitary glands, this could be totally accounted for by their increased water intake.…”
Section: Discussionmentioning
confidence: 99%
“…Some prolactin preparations (produced mainly by the U.S. National Institute of Health) are contaminated with vasopressin (Vorherr, Vorherr & Solomon, 1977;Keeler & Wilson, 1976). However, the Sigma prolactin used in the present study contains very little vasopressin (2-5 ng vasopressin/mg prolactin; Keeler & Wilson, 1976), and this cannot account for its antidiuretic activity (Miller & Van Gemert, 1976). Using Keeler & Wilson's reported level of vasopressin contamination the rate of prolactin administration employed in the present study (7-1 ,g (100 g body wt.)-'.…”
Section: Discussionmentioning
confidence: 99%
“…A problem in the interpretation of many previous reports (e.g. Keeler & Wilson, 1976) is the extremely high doses of prolactin which have been employed. In the present experiments, the dose of prolactin used was calculated to produce a plasma level close to the maximum physiological concentration in the female rat (Lucci et al 1975).…”
Section: Introductionmentioning
confidence: 99%